Transmedia Storytelling in Post-Apocalyptic Fictions: The Case of The last of us - Núñez-Pacheco, Rosa; Barreda-Parra, Aymé; Núñez-Núñez, Marianné (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The purpose of this article is to analyse the transmedia relationships between the video game The Last of Us (Naughty Dog, 2013) and its respective adaptation as a television series produced by Sony Pictures Television and Play Station Production (2023); it also establishes links with Cormac McCarthy's novel The Road (2006) and its film adaptation directed by John Hillcoat in 2009. From the perspective of Comparative Media Studies, the analysis focuses on the transmedia processes that occur between the video game, the television series, the novel, and the film.